The Role of Demandable Debt in Structuring Optimal Banking Arrangements - Calomiris, Charles W.; Kahn, Charles M. (American Economic Review, 1991)
Demandable-debt finance by banks warrants explanation because it entails costs of bank suspension, liquidation, and idle reserve holdings. An explanation is developed in which demandable debt provides incentive-compatible intermediation where the banker has comparative advantage in allocating investment funds but may act against the interests of uniformed depositors. Demandable debt attracts funds by giving depositors an option to force liquidation. Its usefulness in transacting follows from information-sharing between monitors and nonmonitors.